Chromatin insulators and long-distance interactions in Drosophila. - Kyrchanova, O.; Georgiev, P. (FEBS Letters, 2014)
Data on long-distance enhancer-mediated activation of gene promoters and complex regulation of gene expression by multiple enhancers have prompted the hypothesis that the action of enhancers is restricted by insulators. Studies with transgenic lines have shown that insulators are responsible for establishing proper local interactions between regulatory elements, but not for defining independent transcriptional domains that restrict the activity of enhancers. It has also become apparent that enhancer blocking is only one of several functional activities of known insulator proteins, which also contribute to the organization of chromosome architecture and the integrity of regulatory elements.